2013
DOI: 10.1111/cch.12109
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the healthcare experiences of teenaged cancer patients and survivors

Abstract: Understanding teenagers' experiences in the paediatric oncology setting provides information that could be used to shape the delivery of healthcare in a way that is tailored to their needs. Further research in this area is required in order to improve existing oncology care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(79 reference statements)
1
4
0
Order By: Relevance
“…The importance of making friends in the ward also concurred with that of Mitchell et al's (2006) study, whereby 71% of the children and young people felt that making friends with other children with cancer in the ward was important. Akin to previous studies (Farjou et al, 2014;Fern et al, 2013;Mitchell et al, 2006) that highlighted opportunities to interact with other adolescents as an unmet need, the adolescents in our study also reported that they found it hard to make friends in the ward as most patients were babies. The adolescents in this study complained that due to fatigue, visiting specialized facilities such as the teen room was an issue.…”
Section: Discussionsupporting
confidence: 71%
“…The importance of making friends in the ward also concurred with that of Mitchell et al's (2006) study, whereby 71% of the children and young people felt that making friends with other children with cancer in the ward was important. Akin to previous studies (Farjou et al, 2014;Fern et al, 2013;Mitchell et al, 2006) that highlighted opportunities to interact with other adolescents as an unmet need, the adolescents in our study also reported that they found it hard to make friends in the ward as most patients were babies. The adolescents in this study complained that due to fatigue, visiting specialized facilities such as the teen room was an issue.…”
Section: Discussionsupporting
confidence: 71%
“…The results of our study and previous research emphasise that healthcare professionals should be interested and able to adapt care actions to the child’s daily form [ 28 ]. This is further reinforced by Farjou et al [ 29 ], who state children consider the attitude of the healthcare professionals and how they communicate to be important. It turned out that many children wanted the healthcare professionals to be friendly, helpful and caring and have a positive attitude.…”
Section: Discussionmentioning
confidence: 99%
“…Age-appropriate settings and specialist services were often viewed as ideal, but not always available in specific contexts. Identifying service preferences and gaps with AYAs and their families is an important priority for future research and practice development (31,22,16,32,17,18,19,33,29,30). Specifically, the impact that different care environments have on family involvement in care and availability of psychosocial support for both AYAs and their family are areas that require attention.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Ten studies described the need for information and support, leading up to and following a diagnosis of cancer (31,22,16,32,17,18,19,33,29,30). For example, participants reported that healthcare professionals' attitudes and the way they communicated were often inappropriate.…”
Section: Gaps In the Care Deliverymentioning
confidence: 99%
See 1 more Smart Citation